Social Networks Moderate the Syndemic Effect of Psychosocial and Structural Factors on HIV Risk Among Young Black Transgender Women and Men who have Sex with Men - Teixeira da Silva, Daniel; Bouris, Alida; Voisin, Dexter; Hotton, Anna; Brewer, Russell; Schneider, John (AIDS and behavior, 2020)
The interaction between the cumulative effect of psychosocial and structural factors (i.e. syndemic effect) and social networks among young Black transgender women and men who have sex with men (YBTM) remains understudied. A representative cohort of 16–29 year-old YBTM (n = 618) was assessed for syndemic factors [i.e. substance use; community violence; depression; poverty; justice system involvement (JSI)], social network characteristics, condomless anal sex (CAS), group sex (GS), and HIV-infection. The syndemic index significantly increased the odds of CAS, GS, and HIV-infection, and these effects were moderated by network characteristics. Network JSI buffered the effect on CAS, romantic network members buffered the effect on GS, and network age and proportion of family network members buffered the effect on HIV-infection. The proportion of friend network members augmented the effect on GS and HIV-infection. Future research to prevent HIV among YBTM should consider social network approaches that target both structural and psychosocial syndemic factors.